IMPLEMENTASI DAKWAH MELALUI LITERASI DIGITAL DI PONPES MIFTAHUL ULUM GANDOK TASIKMALAYA - Wawan Setiawan; Badrudin; Edi Supriadi; Samsul Arifin; Moh Khoirunnasihin; Imam Abdul Ajiz Asyamsi (An-Nahdliyyah: Jurnal Studi Keislaman, 2022)
In modern life, media plays an important role in social life, especially nowadays cyber media has become one of the basic needs for modern society. This need is also included in the world of da'wah, therefore it is important to understand virtual communities on social media. Doing da'wah activities in the virtual world needs to have digital literacy skills as the basis for running da'wah, this research is important because digital literacy can be used as a bridge in preaching. This study discusses three problem formulations, Miftahul Ulum Islamic Boarding School in Tasikmalaya City uses digital literacy in preaching, and displays da'wah through digital literacy. To reveal the problem thoroughly and in depth, in this study a qualitative method is used which is useful for providing facts and data regarding the communicative actions carried out by the Miftahul Ulum Islamic Boarding School in Tasikmalaya City. Data collection is done by conducting observations, interviews and documentation. Test the validity of the data used in this study is the source triangulation. The results obtained in answering the three problem formulations are: first, the efforts made by the Miftahul Ulum Islamic Boarding School in Tasikmalaya City. is to use awareness of media functions, understanding of media, and media consequences, the model used in digital literacy is in the form of training and cultural awareness. Second, Miftahul Ulum of Tasikmalaya City presented his da'wah to santri, students, and students, who also collaborated with other institutions such as Kominfo, and KPI STAINU. And thirdly, Miftahul Ulum's role in Tasikmalaya City is as an initiator, facilitator, and as a presenter.